(untitled) (Global Journal of Medical Research, 2023)
The development of a child encompasses the definition measurement and assessment of the expected normal patterns at each growth stage corresponding to their age The child s passivity in response to stimuli has wide-ranging effects on a variety of domains including communication skills and consequently cognitive motor and social development Additionally excessive screen time has a negative impact on the sleep-wake cycle which in turn affects learning capacity and attention as well as the risk of heart disease and depression The lack of outdoor activities is closely linked to the growing trend of remote learning which has resulted in an increased substitution of these activities with online games and video apps Additionally the use of electronic devices for more than three hours daily is associated with the worsening of symptoms related to ADHD anxiety and parental stress However following the COVID-19 pandemic and the widespread adoption of remote learning screen time has significantly increased making parental control more challenging while the absence of physical activities has been exacerbated during this period potentially leading to future consequences